Pengaruh Persepsi Manfaat, Persepsi Kemudahan, Persepsi Kenyamanan, Norma Subjektif Dan Kepercayaan Terhadap Minat Menggunakan Electronic Commerce - NINA MONICA; ANNAFI INDRA TAMA (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2017)
This study aims to determine the effect of perceive of usefullnes, perceived ease of use, convenience perception, subjective norms and beliefs to the interest of using electronic commerce in UNISMA students. This research using PLS (Partial Least Square) data analysis technique, with 88 respondents. The results indicate that perceived of usefullness, convenience perception, and beliefs have positif and significant effect to the interest of using e-commerce. Otherwise, perceived ease of use, and subjective norms have no effect.